Does HBA1C Correlate with Lipid Profile in Type 2 Diabetes Mellitus? A New Evidence from Medan, North Sumatera - Julianto, Endy; Silitonga, Hendrika Andriana; Siahaan, Jekson Martiar (Indonesian Journal of Medicine, 2017)
Background: Diabetes mellitus (type 2 DM) is now ranked first in health problems and its prevalence tends to increase worldwide. The Diabetes Control and Complication Trial (DCCT) study showed that lowering HbA1c rates may delay or prevent chronic complications. One of the risk factors for CHD in type 2 DM is dyslipidemia, i.e lipid metabolism disorders in the form of elevated total cholesterol, triglyceride (TG), low-density lipoprotein (LDL), and decreased levels of high-density lipoprotein (HDL). This study aimed to determine the correlation between HBA1C and blood sugar, as well as the lipid profile in patients with type 2 DM.Subject and Methods: This was an analytic observational study with a cross-sectional design. The study was conducted at the Endocrinology and Metabolic polyclinic Pirngadi Hospital, Medan, North Sumatera, from January to February 2018. A total sample of 10 patients diagnosed with type 2 diabetes mellitus with obesity was selected for this study. The independent variables were blood sugar, lipid profile including total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglyceride. The dependent variable was the HbA1c level. Lipid profile was measured by blood serum examination. HbA1c level was measured by blood serum examination. The data were analyzed by Pearson correlation.Results: Hba1c was positively correlated with blood sugar levels and was statistically significant (r= 0.81; p= 0.005). HbA1c correlated weakly and was statistically non-significant with total cholesterol (r= 0.14, p= 0.702), LDL (r= 0.15; p= 0.683), HDL (r= 0.04; p= 0.922), and triglycerides (r= 0.06; p= 0.860).Conclusion: HbA1c correlates with blood sugar levels but does not show a correlation with lipid profiles.Keywords: HBA1C, lipid profile, blood sugar, type 2 diabetes mellitusCorrespondence:Endy Julianto. Department of Parasitology, Faculty of Medicine, Methodist University, Medan.Indonesian Journal of Medicine (2017), 2(3): 207-212https://doi.org/10.26911/theijmed.2017.02.03.08